2D FE–DEM analysis of contact stress and tractive performance of a tire driven on dry sand. (December 2017) - Nishiyama, Kenta; Nakashima, Hiroshi; Shimizu, Hiroshi; Miyasaka, Juro; Ohdoi, Katsuaki
Highlights: 2D FE-DEM was applied to obtain normal and tangential contact stresses. An averaging of contact stresses using stationary segments was introduced. Traction performance of a tire by FE-DEM and by integration using parametric approach became similar. Angle of rotation for maximum normal stress by FE-DEM was shifted forward. Abstract: Normal and tangential stresses acting over a contact interface of a tire driven on dry sand were investigated to expand the applicability of our model incorporating 2D FE–DEM with proportional–integral–derivative (PID) control. A simple averaging method for contact reaction was introduced: computational segments were defined over the lower half part of the tire circumference that translates without rotation with the tire; then the contact stresses were calculated segment by segment. For the analysis, it was assumed that the tire was in rigid contact mode and that it would travel on the model sand terrain in stationary condition. The integration of normal and tangential contact stresses with respect to the angle of rotation was then applied to calculate the vertical contact load, gross tractive effort, net traction, and running resistance of the tire by parametric (or semi-empirical) analysis. The result of tractive performance obtained through the parametric analysis was found to be similar to the result of tractive performance obtained directly using FE–DEM analysis. A forward shift of the consistent angle of rotation for maximum normal contact stress and that for maximum tangential contact stress with the increase of slip from 22% was also observed in the FE–DEM result.